Effects of Optokinetic Stimulation on Verticality Perception Are Much Larger for Vision-Based Paradigms Than for Vision-Independent Paradigms - Dockheer, Katja M.; Bockisch, Christopher J.; Tarnutzer, Alexander A. (Frontiers in Neurology, 2018)
Introduction: Verticality perception as assessed by the subjective visual vertical (SVV) is significantly biased by a rotating optokinetic stimulus. The underlying mechanisms of this effect remain open. Potentially, the optokinetic stimulus induces a shift of the internal estimate of the direction of gravity. This hypothesis predicts a shift of perceived vertical using other, non-vision dependent, paradigms as well. Alternatively, an optokinetic stimulus may only induce a shift of visual orientation, and so would be task-specific. Methods: To test this prediction, both vision-dependent (SVV) and vision-independent (subjective haptic vertical, SHV) paradigms were applied. In 12 healthy human subjects, perceived vertical was measured in different whole-body roll positions (up to ±120°, steps=30°) while watching a clockwise or counter-clockwise rotating optokinetic stimulus. For comparison, baseline trials were collected in darkness. A generalized linear model was applied for statistical analysis. Results: A significant main effect for optokinetic stimulation was noted both for the SVV paradigm (p<0.001) and the SHV paradigm (p=0.013). However, while pairwise comparisons demonstrated significant optokinetic-induced shifts (p≤0.035) compared to baseline in all roll-tilted orientations except 30° and 60° left-ear-down position and counter-clockwise optokinetic stimulation for the SVV paradigm, significant shifts were found in only 1 of the 18 test conditions (120° left-ear-down roll orientation, counter-clockwise optokinetic stimulation) for the SHV paradigm. Compared to the SHV, the SVV showed significantly (p<0.001) larger shifts of perceived vertical when presenting a clockwise (15.3±16.0° vs. 1.1±5.2°, mean±1 standard deviation) or counter-clockwise ((-12.6±7.7° vs. -2.6±5.4°) rotating optokinetic stimulus. Conclusion: Comparing the effect of optokinetic stimulation on verticality perception in both vision-dependent and vision-independent paradigms, we demonstrated distinct patterns. While significant large and roll-angle dependent shifts were noted for the SVV, offsets were minor and reached significance only in one test condition for the SHV. These results suggest that optokinetic stimulation predominately affects vision-related mechanisms, possibly due to induced torsional eye displacements, and that any shifts of the internal estimate of the direction of gravity are relatively minor.